Promoting gender, equity, human rights and ethnic equality in neglected tropical disease programmes. (13th January 2021) - Mbabazi, P S; Del Pino, S; Ducker, C; Dean, L; Broekkamp, H; Prasetyanti, W; Jacobson, J; Krentel, A; Seunik, M; Bustinduy, A L; Malecela, M
Abstract: Limited attention to tackling neglected tropical diseases (NTDs) through the lenses of gender, equity, ethnicity and human rights inadvertently undermines progress due to the exclusion of subgroups in populations living in conditions of vulnerability. Supporting national NTD programmes to make equity analysis part of their routine activities and revitalising intersectoral collaboration will be essential to achieve effective, sustainable service delivery with a person-centred approach. Gender, equity, human rights and ethnic equality for NTD programmes should therefore be incorporated in multisectoral engagements.